Survey of optimal motion planning. Issue 1 (22nd September 2020) - Yang, Yajue; Pan, Jia; Wan, Weiwei
Abstract : Optimal motion planning becomes more and more important these days and is critical for motion planning algorithms developed in the academia to be applicable to real‐world applications. The objective of this article is to survey the current state‐of‐the‐art on optimal motion planning algorithms in terms of their three main components: the decision variables and problem formulation, constraints, and objectives. A selection of proposed techniques is reviewed along with a discussion of their effectiveness and limitations. The side‐by‐side comparison presented in this survey helps to gain insight into the strengths and limitations of the reviewed approaches and assists with system‐level design choices.